A STUDY ON THE MGNREGA PROGRAMME WITH SPECIAL REFERENCE TO SOUTHERN KERALA - Vilvijaya, Anupama; Manikantan, Anupama; B, Nethra; S, Jayashree (International Journal of Psychosocial Rehabilitation, 2020)
The paper attempts to study on the government policy, Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA) in Grama Panchayats of Pathiyoor and Krishnapuram of Alappuzha district and Chavara and Thazhava of Kollam district. The planning arrangement and implementation have been looked upon in the study of this scheme. The scheme by government of Kerala has also been examined and studied based on various aspects such as their rules regulations and guidelines. The women were the majority and are benefited the most from this programme and their registration in all the three panchayats are high. The worker’s registration is also relatively high in this policy. It has accomplished in raising the rural employment level and the income in rural households. Hence it has increased the buying power of them. The women who work in groups has strengthened the women empowerment. This scheme shows good promise in the field of economic growth and the study has suggested various ways to improve the programme and make it more efficient.